Profil Metabolit Sekunder, Fenolik Total, Aktivitas Antibakteri dan Antijamur Ekstrak Daun Sungkai (Peronema canescens Jack) Dari Daerah Bengkulu dan Pariaman - -, Norman Ferdinal; Fischa A., Wulandari; Suryati, Suryati (Departemen Kimia Universitas Andalas, 2024)
Indonesian people have long recognized and utilized plants that have medicinal properties to overcome health problems. One of the medicinal plants that grow in Indonesia and is commonly used by the community is the Sungkai plant (Peronema canescens Jack). This Sungkai plant is spread across the island of Sumatra including Bengkulu and Pariaman regions. This study used methanol, ethyl acetate, and hexane extracts of sungkai leaves growing in Bengkulu and Pariaman areas for phytochemical screening, total phenolic content using the Folin-Ciocalteu method, and determination of antibacterial activity against Escherichia coli and Staphylococcus aureus bacteria, as well as determination of Candida albicans antifungal activity using the well diffusion method. The results showed that sungkai leaf extract contained phenolics, flavonoids, saponins, steroids, and alkaloids. The methanol extract of sungkai leaves from Bengkulu and Pariaman had the highest total phenolic content of 175.3671 mg GAE/g sample and 227.7021 mg GAE/g sample, respectively. In the antibacterial activity test, the ethyl acetate extract of sungkai leaves from Bengkulu and Pariaman produced the largest inhibition zone with moderate criteria, namely 5.22 mm and 6.38 mm against Escherichia coli and Staphylococcus aureus obtained inhibition zones of 7.13 mm and 6.08 mm. The antifungal activity showed the largest inhibition zone in the ethyl acetate extract of sungkai leaves from Bengkulu and Pariaman regions, namely 5.22 mm and 6.40 mm, which are included in the moderate category.